(untitled) (Research, Society and Development, 2022)
This is a morphometric analysis of maxillary central incisors to aid in the planning of immediate implants. The literature reviewed did not show an implant design that would allow for optimal conditions for immediate insertion. A group comprising 25 extracted maxillary central incisors was investigated (Group 1) and Group 2, corresponding to two implant models, Alvim® Cone-Morse and Drive® Cone-Morse, indicated for immediate replacement of maxillary central incisors. In group 1, direct measurements with the aid of a digital caliper were performed. For group 2, two-dimensional images of the implants were vectorized by software, enabling measurements and comparative analyzes with group 1. After the statistical analysis, the ratio found between the averages of the alveolar diameters, at an apical location of -4mm from the cemento- enamel (1mm intraosseous) was 1.06. Thus, periapical radiography may suggest relatively safe values for predicting dimensions visible only on computed tomography. The findings revealed that gaps will be present for all implant platforms compared. After the measurements, an implant model biomechanically compatible with the supposed alveoli could present, in its configuration, a platform measuring 6.5mm in diameter, with varying heights, where regardless of height, the diameter at 6mm of its platform would be 4.5mm. For the sample taken in the study, this implant pattern would facilitate a primary locking of the implants in the region comprised in 24 alveolus (96%). The study revealed a large discrepancy between the supposed alveoli and conformations of investigated implants.